Nineteenth-Century Canada and Australia: The Paradoxes of Class Formation - Palmer, Bryan (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
This speculative essay presents a preliminary statement on the paradoxical character of 19th-century class formation in the two white settler dominions of Canada and Australia. Outposts of empire, these social formations were early regarded with disdain, the one a classic mercantilist harvester of fish, fur, and wood, the other a dumping ground for convicts. By the mid-to-late 19th-century, however, Canada and Australia were the richest of colonies. Within their distinctive cultures and political economies, both supposedly dominated by staples, emerged working classes that were simultaneously combatative and accommodated. By the 1880s impressive organizational gains had been registered by labour in both countries, but the achievements of class were conditioned by particular relations of fragmentation, including those of 'race' and gender.